PROGRAMMATIC ADVERTISING: Evolution, Efficacy, and Ethical Implications In The Digital Age - Onni Meirezaldi (Journal Publicuho, 2023)
The digital landscape has witnessed significant transformations over the past few decades, with programmatic advertising emerging as a pivotal force reshaping the world of brand communication. This article delves deep into the evolution of online advertising, highlighting the inefficiencies of traditional digital ad-buying methods that paved the way for the algorithmic and data-driven paradigm of programmatic advertising. While offering advantages like precision targeting, automation, scalability, and real-time analytics, programmatic advertising has challenges, especially concerning data privacy, regional nuances, and ethical considerations. Through a lens of global and regional case studies, the article underscores the intricate dynamics and cultural sensitivities crucial for successful campaigns. As we stand at the cusp of technological advancements, integrating Artificial Intelligence, Augmented Reality, and 5G into the programmatic ecosystem promises further evolution. The article concludes with robust recommendations for researchers, emphasizing the importance of interdisciplinary studies, ethical considerations, and the need for continuous adaptation in this ever-evolving digital world.